“If They Were Important, We Would Have Heard About Them”: Inuit History Beyond Canadian Mythology - Stoller, Mark; Ullulaq, Jennifer; Okpik, Barbara (Études Inuit Studies)

(untitled) (Centre interuniversitaire d’études et de recherches autochtones (CIÉRA), 2022)
The community of Gjoa Haven/Uqsuqtuuq has recently received national and international attention for its proximity to the lost ships of the nineteenth century Franklin expedition. The locating of Franklin’s ships in 2014 and 2016 has been followed by celebrations of the role of Inuit knowledge in finding the wrecks, and thought to hold promise for how Inuit and Western research partnerships are conducted. Yet many people in Gjoa Haven, and particularly its youth, have little knowledge of or interest in the Franklin story. Locally, Franklin stores are associated with Qablunaat (non-Inuit) interests in northern history, but they are not representative of Inuit history. We examine the relationship between Inuit and Qablunaat history in Gjoa Haven, with a focus on what is important to its youth. Although Franklin stories are of limited importance in Inuit history, they continue to influence how Inuit are perceived by non-Inuit and present obstacles to informing Qablunaat about Inuit history and culture. As young Inuit have more opportunities to interact with Qablunaat, the subject of history offers space for these youth to articulate their own views and priorities for learning and sharing northern stories.